Prevalence of musculoskeletal low back pain among registered nurses: Results of an online survey - Gilchrist, Andrea; Pokorná, Andrea (Journal of clinical nursing, 2021)
AIMS AND OBJECTIVES: The aim of this study was to describe the prevalence of low back pain (LBP) and the use of lifting aids and ergonomics among Czech registered nurses. BACKGROUND: Low back pain is the most common occupational health problem affecting nurses. Frequent manual lifting of heavy loads, including patients, is one of the main duties of nursing staff, which causes compressive and shear forces on the vertebrae of the lower spine. Training in manual handling and lifting aids reduce the physical burden on the musculoskeletal system, thus decreasing work-related back injuries and further back problems. DESIGN: A cross-sectional survey. METHODS: The online survey was distributed to 1460 randomly selected nurses involved in caring for patients. The survey comprised the extended version of the Nordic Musculoskeletal Questionnaire and a self-structured questionnaire. Data were analysed using STATA 15 at a significance level of 0.05. RESULTS: Of the 569 respondents, 84.7% reported high occurrence of LBP over the previous 12-month period. The lower back was the most commonly reported body region for pain, followed by the neck, shoulders and upper back. LBP was found to occur significantly less among nursing staff who used mechanical lifting aids. Nurses with a higher level of education were found significantly more likely to use mechanical patient-lifting equipment in their clinical practice. CONCLUSIONS: The study findings show that LBP is a frequent problem among nurses and has highlighted a lack of organisational safety practices and culture in clinical nursing practice. RELEVANCE TO CLINICAL PRACTICE: This study provides valuable information about the extent of LBP among nurses with insufficient preventive measures or health and safety practices at work. The results provide useful baseline data for the Czech Republic, that may lead to increased awareness and therefore implementation of preventative strategies, and thus enable a reduction in the risk of back injuries among nursing professionals.
Keywords: Surveys and Questionnaires; Nurses; Humans; health risks; Occupational Diseases; prevalence; rizikové faktory; registered nurses; nemoci z povolání; lidé; musculoskeletal; Low Back Pain; pain; průzkumy a dotazníky; zdravotní sestry; lumbalgie; Czech Republic; ergonomics; Cross-Sectional Studies; Prevalence; survey; Česká republika; průřezové studie; Risk Factors